TRANSFORMASI NILAI BUDAYA TUDANG MANDRE SIPULUNG PADA ETNIS BUGIS DI DESA TELUK PAKEDAI HULU - Surahman Ardiansyah; Yohanes Bahari; Amrazi Zakso (Universitas Tanjungpura, 2021)
AbstractThis research aims to describe the culture of Tudang Manre Sipulung, Bugis ethnic, as a heritage in Teluk Pakedai Hulu Village which experienced a cultural value transformation. In the process of describing the four sub-problems related to early cultural values, the form of transformation of present cultural values, then the factors causing the transformation, and the regeneration of the cultural value heritage of Tudang Manre Sipulung. through a narrative approach to obtain primary data obtained from traditional and religious leaders through observation and in-depth interviews to reduce data and get a good data presentation. The results of research related to early cultural values originate from religiosity asking for protection of natural spirits, then in the transformation of cultural values that prioritizes gratitude to Allah SWT as the creator of nature, from the causecultural transformation lies at the level of gratitude, kinship, changes in economic and moral values from environmental influences. In the process of cultural regeneration of Tudang Manre Sipulung, it is seen from the internalization of culture at home, the socialization of Islamic cultural values and enculturation as a medium for exchanging information in the life of a cultured society.Keywords: Transformation, of Culture Values, Tudang Manre Sipulung